The Conflict Between Reason and Faith: The Formation of The Universe Based on The Theories of Creation and Evolution - Romandya, Natanael Juan; Manurung, Freddy (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The conflict between reason and faith in understanding the universe's origins has been the subject of long-standing debate in various religious and scientific communities. This article undergoes an in-depth analysis of the two main views that define different views of the creation of the universe: creation theory and evolutionary theory. The first approach, which is based on creation theory, asserts that the universe was created by God in accordance with sacred texts, such as the Book of Genesis in the Bible. This view emphasizes the role of faith and religious beliefs in describing the universe's origins. This view interacts with modern scientific discoveries and how potential conflicts between religious beliefs and scientific evidence can be resolved. On the other hand, the evolutionary view relies on the origins of the universe on an ongoing evolutionary process, based on ever-growing scientific evidence. The theory of evolution views the creation of the universe as a process that took place over millions of years through biological and physical evolution. This concept influences religious views and how efforts are made to ease tensions between scientific views and religious faith.